The Meaning of Having an Autistic Child in Malay Family Indonesia - Jiu, Cau Kim; Rungreangkulkij, Somporn (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2019)
The condition of families with autistic children raises many views and judgments both from family and society. This ethnographic study aimed to describe the meaning of families and communities towards families with autistic children. Data were collected through focus group discussions and in-depth interviews. Key informants come from families who have autistic children and community members recruited by purposive sampling, while the data were analyzed using thematic analysis. This study results generate  two categories of perception of the meaning of having autistic children.  The first category was made by the families which comprises four themes such as 1) A test from God, 2) Destiny of God, 3) Autistic children different with other children, and 4) Children who need intensive helping. The second category was the perception made by the community members which consists of two themes, such as 1) Test for family, and 2) An autistic child as a holy child. This study further shows that  culture is believed to determine how families and the members of the community perceive and interpret the existence of autistic children in the families so that it is very important for health workers to understand the culture that exists in the community.